Photonic biosensor chip for early-stage cancer diagnosis - Najeeb, Najla; Zhang, Yaping; Mellor, Christopher J.; Benson, Trevor M. (2015)
This paper introduces a generic design of a silicon on silica “lab on a chip” photonic biosensor for medical diagnosis applications, and especially for early-stage cancer diagnosis. The sensitivity of detection of the biosensor developed is at least 10 - 100 times more sensitive than that of current commercial biosensors.